Lean Construction: An Effective Approach for Project Management - Ansah, Richard Hannis; Sorooshian, Shahryar; Shariman, Mustafa (Asian Research Publishing Network (ARPN), 2016)

(untitled)
red within a specified time. It has been asserted by a number of researchers that fast, complex and uncertain projects cannot be managed through the conventional ways and that fast track projects with long, complicated supply chains involving many players and subject to multiple, extensive process design changes have complex flow management that have failed miserably. The conceptual models of construction management and the tools it utilizes (work breakdown structure, critical path method, and earned value management) have been criticized to be deficient in handling the present unique challenges of projects. As a result, the industry is characterized by a number of wastes including: overproduction, lead time, transportation, inappropriate processing, inventories, unnecessary movements, rework and making do wastes. There is therefore the need for practical and robust models and techniques that will help projects teams deal with the issues of wastes in projects. This can only be achieved through the adoption of lean production systems in the construction industry, thus, Lean Construction (LC). In this paper, LC approach and the importance for its implementation has been discussed as the robust approach for project management.